Peripheral blood immune cells from individuals with Parkinson's disease or inflammatory bowel disease share deficits in iron storage and transport that are modulated by non-steroidal anti-inflammatory drugs - MacKenzie L. Bolen; Beatriz Nuñes Gomes; Blake Gill; Kelly B. Menees; Hannah Staley; Janna Jernigan; Nikolaus R. McFarland; Ellen M. Zimmermann; Christopher E. Forsmark; Malú Gámez Tansey (Neurobiology of Disease)
Parkinson's Disease (PD) is a multisystem disorder in which dysregulated neuroimmune crosstalk and inflammatory relay via the gut-blood-brain axis have been implicated in PD pathogenesis. Although alterations in circulating inflammatory cytokines and reactive oxygen species (ROS) have been associated with PD, no biomarkers have been identified that predict clinical progression or disease outcome. Gastrointestinal (GI) dysfunction, which involves perturbation of the underlying immune system, is an early and often-overlooked symptom that affects up to 80 % of individuals living with PD. Interestingly, 50–70 % of individuals with inflammatory bowel disease (IBD), a GI condition that has been epidemiologically linked to PD, display chronic illness-induced anemia — which drives toxic accumulation of iron in the gut. Ferroptotic (or iron loaded) cells have small and dysmorphic mitochondria—suggesting that mitochondrial dysfunction is a consequence of iron accumulation. In pro-inflammatory environments, iron accumulates in immune cells, suggesting a possible connection and/or synergy between iron dysregulation and immune cell dysfunction. Peripheral blood mononuclear cells (PBMCs) recapitulate certain PD-associated neuropathological and inflammatory signatures and can act as communicating messengers in the gut-brain axis. Additionally, this communication can be modulated by several environmental factors; specifically, our data further support existing literature demonstrating a role for non-steroidal anti-inflammatory drugs (NSAIDs) in modulating immune transcriptional states in inflamed individuals. A mechanism linking chronic gut inflammation to iron dysregulation and mitochondrial function within peripheral immune cells has yet to be identified in conferring risk for PD. To that end, we isolated PBMCs and simultaneously evaluated their directed transcriptome and bioenergetic status, to investigate if iron dysregulation and mitochondrial sensitization are linked in individuals living with PD or IBD because of chronic underlying remittent immune activation. We have identified shared features of peripheral inflammation and immunometabolism in individuals living with IBD or PD that may contribute to the epidemiological association reported between IBD and risk for PD.